2018
DOI: 10.1159/000492317
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tumor-Suppressor, CDH18, Inhibits Glioma Cell Invasiveness Via UQCRC2 and Correlates with the Prognosis of Glioma Patients

Abstract: Background/Aims: CDH18 (cadherin 18) is specifically expressed in the central nervous system and associated with various neuropsychiatric disorders. In this study, the role of CDH18 in glioma carcinogenesis and progression was investigated. Methods: The expression of CDH18 and its prognostic value in patients with gliomas were analyzed in public database and validated by real-time PCR/immunohistochemical staining (IHC) in our cohort. CCK-8 assay, transwell migration assay, wound healing assay, clonogenic assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…The gene is located on chromosome 5, and it is reported to be highly expressed specifically in the brain, with higher expression in different parts of the Central Nervous System (CNS), including middle temporal gyrus, cerebellum and frontal cortex 35 . The gene is associated with several neuropsychiatric disorders, as well as glioma, the most common CNV tumor among adults 36 . Looking at glioma cells, and through in vitro and in vivo functional experiments, Bai et al 36 showed that CDH18 acts as a tumor suppressor through the downstream gene target UQCRC2, and suggested targeting CDH18 in glioma treatmen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene is located on chromosome 5, and it is reported to be highly expressed specifically in the brain, with higher expression in different parts of the Central Nervous System (CNS), including middle temporal gyrus, cerebellum and frontal cortex 35 . The gene is associated with several neuropsychiatric disorders, as well as glioma, the most common CNV tumor among adults 36 . Looking at glioma cells, and through in vitro and in vivo functional experiments, Bai et al 36 showed that CDH18 acts as a tumor suppressor through the downstream gene target UQCRC2, and suggested targeting CDH18 in glioma treatmen.…”
Section: Discussionmentioning
confidence: 99%
“…The gene is associated with several neuropsychiatric disorders, as well as glioma, the most common CNV tumor among adults 36 . Looking at glioma cells, and through in vitro and in vivo functional experiments, Bai et al 36 showed that CDH18 acts as a tumor suppressor through the downstream gene target UQCRC2, and suggested targeting CDH18 in glioma treatmen. Moreover, CDH18 was reported in a meta-analysis of depression personality trait association as the nearest gene to rs349475 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, JAZF1 was found to control the biological behaviours of many tumors as endometrial sarcomas and cancer prostate, and it was considered a tumor suppressor (Hodge et al, 2016, Hazelett et al, 2014. Tumor suppressors have participated in many biological cellular activities as cell proliferation, apoptosis and control of cell cycle (Pospiechet al, 2018, Qiu et al, 2018, Nikbakht et al, 2018, Bai et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The gene is located on chromosome 5, and it is reported to be highly expressed specifically in the brain, with higher expression in different parts of the Central Nervous System (CNS), including middle temporal gyrus, cerebellum and frontal cortex 24 . The gene is associated with several neuropsychiatric disorders, as well as glioma, the most common CNV tumor among adults 25 . Looking at glioma cells, and through in vitro and in vivo functional experiments, 25 et al showed that CDH18 act as a tumor suppressor through the downstream gene target UQCRC2, and they suggested targeting CDH18 in the gliomas treatment discovery.…”
Section: Discussionmentioning
confidence: 99%
“…The gene is associated with several neuropsychiatric disorders, as well as glioma, the most common CNV tumor among adults 25 . Looking at glioma cells, and through in vitro and in vivo functional experiments, 25 et al showed that CDH18 act as a tumor suppressor through the downstream gene target UQCRC2, and they suggested targeting CDH18 in the gliomas treatment discovery. Moreover, CDH18 was reported in a meta-analysis of depression personality trait association as the nearest gene to rs349475 26 .…”
Section: Discussionmentioning
confidence: 99%